From Clumsy to Conqueror: Po’s Archetypal Ascension in Kung Fu Panda 3 (2016) Movie - Steinlie, Granardo; Pane, Charrine Sefanya Fiorentina; Jesua, Clement Wei; Chay, Oline Manuel (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study investigates the archetypal dimensions of Kung Fu Panda 3 (2016) through the lens of Jungian archetype theory and Campbell’s Hero’s Journey framework. Using a qualitative method, specifically archetypal criticism, the analysis focuses on how Po’s transformation from a clumsy panda into the Dragon Warrior reflects universal patterns of self-discovery, individuation, and moral growth. The study examines selected scenes, dialogues, and visual symbolism, supported by secondary literature on archetypal theory. The findings reveal three significant results: 1) Po’s development embodies the Hero’s Journey archetype, in which he overcomes trials, confronts his shadow figure (Kai), and achieves individuation by integrating his conscious and unconscious selves. 2) the binary opposition between Hero and Shadow illustrates Jung’s psychological principles, where Po’s strength emerges not from domination but from unity, mentorship, and acceptance of vulnerability. 3) the film functions as children’s literature by embedding moral lessons of identity, courage, and community into an accessible narrative, thereby reinforcing its educational value beyond entertainment. In conclusion, the study demonstrates that Kung Fu Panda 3 communicates timeless archetypal patterns that resonate across cultural contexts, offering insights into human development while serving as a didactic tool for younger audiences. These results affirm the enduring relevance of archetypes in both literary and cinematic storytelling.